2017
DOI: 10.1089/tmj.2016.0082
|View full text |Cite
|
Sign up to set email alerts
|

Using Video from Mobile Phones to Improve Pediatric Phone Triage in an Underserved Population

Abstract: Obtaining mobile phone videos for telephone triage is acceptable to families, feasible, and may help improve the quality of telephone triage in an urban, minority population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…A Danish study on neonatal tele-homecare showed that telehealth service provided the parents with increased reassurance and empowerment [ 27 ]. Video transmission of children with asthma exacerbation from parents’ smartphones in a hospital waiting area to health care staff was feasible and appreciated by parents and health professionals [ 28 ]. The American Academy of Pediatrics has encouraged increased use of telemedicine to enhance access to pediatric care and address physician shortages [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A Danish study on neonatal tele-homecare showed that telehealth service provided the parents with increased reassurance and empowerment [ 27 ]. Video transmission of children with asthma exacerbation from parents’ smartphones in a hospital waiting area to health care staff was feasible and appreciated by parents and health professionals [ 28 ]. The American Academy of Pediatrics has encouraged increased use of telemedicine to enhance access to pediatric care and address physician shortages [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The domain-specific discussions of results, research gaps, and future research opportunities are presented in the domain-specific sections in Multimedia Appendix 3 [ 2 , 3 , 5 , 8 , 10 , 13 , 22 - 24 , 28 , 31 , 33 , 34 , 55 , 58 , 59 , 64 , 66 - 70 , 73 , 75 , 76 , 78 , 83 - 85 , 87 - 90 , 92 , 96 , 102 , 113 , 118 , 120 , 121 , 123 , 125 - 132 , 144 - 146 , 155 , 156 , 168 , 169 , 176 , 179 , 181 , 189 , 196 , 211 , 212 , 228 , 229 , 231 , 239 , 240 , 248 , 297 , 327 , 333 , 343 , 353 , 374 , 375 , 384 - 411 ], and the future research opportunities are summarized in…”
Section: Discussionmentioning
confidence: 99%
“…Videoconferencing is a technology-enabled communication method that allows 2 or more participants to see and hear each other in real-time over the internet� 73,74 Videoconferencing technology has been incorporated into a variety of health care services across Canada to facilitate remote consultations, virtual appointments, and telemedicine initiatives� 75,76 However, apart from Alberta's Health Link 811, provincial and territorial telephone triage programs have not yet adopted videoconferencing as a form of intake� 7 Based on the findings of international studies that have examined the effects of incorporating videoconferencing software in various triage processes, [77][78][79][80][81] the implementation of videoconferencing technology into telephone triage programs could enable visual examination, facilitate nonverbal communication, and foster greater patient engagement between users and health care professionals, allowing for more comprehensive and accurate assessments� In some situations, videoconferencing technology has the potential to improve the efficiency of services by reducing the time required for patient assessments� 77 For example, nurses conducting virtual assessments of patients' health status and symptoms may be able to quickly identify signs of distress or emergent conditions through visual cues that would not be available in audio-only conversations� 79 In 2020, the Yorkshire Ambulance Service in the UK piloted the use of videoconference technology for "hear and treat" consultations, which is similar to the health information and advice services offered through telephone triage programs in Canada� 81 Their 2021 study 81 concluded that video triage for low-acuity calls had high levels of patient satisfaction compared to standard telephone triage� Furthermore, clinical staff reported that video triage improved clinical assessment and decision-making compared to telephone alone� 81…”
Section: Videoconferencingmentioning
confidence: 99%